Mathematical simulation and optimization of cutting mode in turning of workpieces made of nickel-based heat-resistant alloy; Journal of Physics: Conference Series; Vol. 1015 : Information Technologies in Business and Industry (ITBI2018) - Bogoljubova M. N. Mariya Nikitichna; Afonasov A. I. Aleksey Ivanovich; Kozlov B. N.; Shavdurov D. E. (Techniques and technologies of the automated mechanical engineering, 2018)
Title screen